Өрмөгтэй формацын гарал үүслийн судалгаа - Ц.Оюунболд; Л.Жаргал (Geological Issues, 2023)
Early Carboniferous Urmugtei Formation is widely distributed in Kharaa terrane, Khangai-Khentii Belt and consists of marine conglomerate, sandstone and siltstone. The purpose of this study is to identify provenance of Urmugtei formation based on petrological, geochemical and geochronological studies of sandstone, collected from the formation. The sandstone of Urmugtei formation is classified into three types: lithic arkose, feldspathiclitharenite, and arkose composition. QFL discrimination diagram of the samples indicates that Urmugtei formation sandstone was derived from the transitional magmatic arc setting. As the results of major element oxides, sandstone samples are characterized by intermediate to acidic composition (andesite to dacite) suggesting continental island arc environment. Geochronological studies show 238U/206 Pb Concordia age of 356-365 Ma, indicating that sandstone source was formed in Late Devonian to early Carboniferous time.